Early treatment with sumatriptan prevents PACAP38-induced migraine: A randomised clinical trial. (May 2021) - Wienholtz, Nita Katarina Frifelt; Christensen, Casper Emil; Zhang, Ditte Georgina; Coskun, Hande; Ghanizada, Hashmat; Al-Karagholi, Mohammad Al-Mahdi; Hannibal, Jens; Egeberg, Alexander; Thyssen, Jacob P; Ashina, Messoud
Objective: To determine whether early treatment with sumatriptan can prevent PACAP38-induced migraine attacks. Methods: A total of 37 patients with migraine without aura were enrolled between July 2018 to December 2019. All patients received an intravenous infusion of 10 picomole/kg/min of PACAP38 over 20 min followed by an intravenous infusion of 4 mg sumatriptan or placebo over 10 min on two study days in a randomised, double-blind, placebo-controlled, crossover study. Results: Of 37 patients enrolled, 26 (70.3%) completed the study and were included in analyses. Of the 26 patients, four (15%) developed a PACAP38-induced migraine attack on sumatriptan and 11 patients (42%) on placebo ( p = 0.016). There were no differences in area under the curve for headache intensity between sumatriptan (mean AUC 532) and placebo (mean AUC 779) ( p = 0.35). Sumatriptan significantly constricted the PACAP38-dilated superficial temporal artery immediately after infusion (T30) compared with infusion of placebo ( p < 0.001). Conclusions and relevance: Early treatment with intravenously administered sumatriptan prevented PACAP38-induced migraine. Prevention of migraine attacks was associated with vasoconstriction by sumatriptan in the earliest phases of PACAP provocation. These results suggest that sumatriptan prevents PACAP38-induced migraine by modulation of nociceptive transmission within the trigeminovascular system. Trial Registration: ClinicalTrials.gov (NCT03881644).